Fiscal Competition in Space and Time - David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper analyzes fiscal competition among numerous spatially- separated jurisdictions in an explicitly dynamic framework. The degree of factor mobility between jurisdictions is imperfect because it is costly and time-consuming to adjust factor stocks. Even if it is harmful in the long run, a jurisdiction's residents can benefit in the short run from taxing mobile factors owned by non-residents. The optimal tax on mobile factors is lower, the faster the speed with which factors adjust to fiscal policy. Anticipated taxes are less beneficial than those that can be imposed unexpectedly.
Keywords: H00; R00; 330